The Role of Philosophy in the Development of Strategies for Ensuring Mental Security in the Conditions of “Hybrid Wars” of Our Time - Andrey A. Kovalev (Гуманитарный вектор)
The practice of the last decade has exacerbated the problem of mental security to the limit within the framework of the general system of national security of the state. To solve this problem, a comprehensive interdisciplinary approach is needed, in which philosophy can take a key position as an integration center of social and humanitarian knowledge. The revival of the significance of philosophy in the face of the challenges and threats of the 21st century forms a serious potential for overcoming them. The “hybridization” of modern wars forces us to abandon stereotyped solutions, rethink values and develop effective strategies to ensure mental security. The purpose of the study is to study mental wars as an element of modern “hybrid wars” and offer a number of recommendations that can be used in the development of mental security strategies. In the 21st century, despite the generally high level of physical security of states, the mental level of national security remains under threat due to the hybridization of modern wars. The analysis of philosophical concepts and the allocation on their basis of the fundamental principles of ensuring mental security will strengthen national security in general, as well as increase the level of competitiveness of the nation in the context of the growing trend of “hybrid wars”. We carried out an interdisciplinary analysis of philosophical concepts and principles that can be used in the context of mental security. Mental wars have become a challenge to the modern nation-state and the entire system of the world order. Turning to philosophy as a discipline that can unite the nation by strengthening the national mentality by creating a kind of mental immunity will help move forward in matters of ensuring mental security in the conditions of “hybrid wars” of our time.